Pure Pursuit Model When The Vehicle Following The X and Y Axis and Stanley Model - SİEF Addeen Yacoub A Shabaneh; APROF. DR. Metin Ahmet Ergeneman (Genius Journals, 2023)
The path following is an important topic for autonomous vehicle and its wide used in robotic fields .The main objective of the project is to study the vehicle’s tracking of a point on the x and y axes theoretically and using the MATLAB simulation program, This study is concerned with determining the look-ahead distance using the driving scenario, as well as the curvature of the path by drawing the path and applying pure pursuit controller, and it is determined automatically. And by using the Pure Pursuit Model and in addition to the Stanley Model, where the study was conducted under certain conditions and the vehicle’s parameters were changed to see the results and certain points were set for the vehicle to follow where It was found that when the value of the point being tracked decreases, a state of instability occurs under all conditions, in addition to studying the change in the center of gravity and its effect on the stability of the vehicle.
Keywords: Pure Pursuit; Stanley; Look Ahead Distance